Synthesis of the C19-C34 segment of amphidinolide C - Mohapatra, Debendra K.; Rahaman, Hasibur; Chorghade, Mukund S.; Gurjar, Mukund K. (Synlett, 2007)
The synthesis of the C19-C34 segment of amphidinolide C is described. The key steps include the Mioskowski's Lewis acid catalyzed epoxide opening with the alcohol, ring-closing metathesis, Wittig reaction, and Nozaki-Hiyama-Kishi coupling reaction.
Keywords: amphidinolide C; Cytotoxic; Nozaki-Hiyama-Kishi coupling; Ring-closing metathesis; Wittig reaction

Synthesis of the C14-C29 segment of amphidinolide U utilizing a tandem dihydroxylation-S(N)2 cyclization protocol - Mohapatra, Debendra K.; Rahaman, Hasibur (Synlett, 2008)
The synthesis of the C14-C29 subunit of amphidinolide U is described. The key steps include the trans-2,5-disubstituted tetrahydrofurans via a highly diastereoselective and high yielding tandem dihydroxylation-S(N)2 cyclization, Wittig reaction, and Nozaki-Hiyama-Kishi coupling reaction.
Keywords: amphidinolide U; Cytotoxic; Nozaki-Hiyama-Kishi coupling; tandem dihydroxylation-S(N)2 cyclization; Wittig reaction

Stereoselective synthesis of the densely functionalized C1-C9 fragment of amphidinolides C and F - Mohapatra, Debendra K.; Dasari, Pavankumar; Rahaman, Hasibur; Pal, Rita (Tetrahedron Letters, 2009)
The synthesis of the C1-C9 subunit of amphidinolides C and F is described. Key steps include tandem Sharpless asymmetric dihydroxylation-S(N)2 cyclization reaction, Lewis acid-mediated epoxide opening, Wittig reaction, and Wacker oxidation. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Amphidinolide C and F; Cytotoxic; Tandem dihydroxylation-S(N)2; Wacker oxidation; Wittig reaction

Stereoselective formal total synthesis of novel antibiotic (-)-centrolobine - Mohapatra, Debendra K.; Pal, Rita; Rahaman, Hasibur; Gurjar, Mukund K. (Heterocycles, 2010)
A concise and stereoselective formal total synthesis of (-)-centrolobine is achieved utilizing Mioskowski's Lewis acid mediated epoxide opening followed by ring-closing metathesis as the key reaction.
Keywords: antibiotic; Centrolobine; Keck allylation; Ring-closing metathesis; Sharpless asymmetric epoxidation

Synthetic studies of superstolide A: a carbohydrate based synthesis of the C21-C26 segment - Pal, Rita; Rahaman, Hasibur; Mohapatra, Debendra K.; Gurjar, Mukund K. (Letters in Organic Chemistry, 2010)
The synthesis of C21-C26 fragment of superstolide A, starting from D-glucose diacetonide, involving regioselective ring opening of epoxide by Grignard reagent and regioselective stereospecefic hydroboration oxidation has been described.
Keywords: Chiral pool; Potent cytotoxic; Regioselective epoxide opening; Stereoselective hydroboration-oxidation; Superstolide A